2001
DOI: 10.1007/s005950170169
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment and Subsequent Outcome of Patients with Carcinoma of the Splenic Flexure

Abstract: Extended resection, comprising extended right hemicolectomy, splenectomy, and distal pancreatectomy, has been advocated for carcinoma of the splenic flexure because the lymphatic drainage at this site is variable. The present study addresses the problems associated with selecting the most appropriate operative procedure to achieve cure of splenic flexure cancers. We conducted a retrospective review of 27 patients with splenic flexure cancer who underwent curative resection. Left partial colectomy was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
42
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 13 publications
4
42
0
1
Order By: Relevance
“…Some surgeons have argued that subtotal colectomy or extended right hemicolectomy improves oncological outcome (7,13). However, other studies have demonstrated that the prognosis for left hemi-colon cancer is no worse than for other colon cancers, and that left hemi-colectomy is sufficient for a satisfactory oncological outcome (8,9,14). A recent study showed that complete mesocolic excision in the mesocolic plane with central vascular ligation is associated with the removal of more mesocolon and a greater lymph node yield, and might improve 5-year survival (15).…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons have argued that subtotal colectomy or extended right hemicolectomy improves oncological outcome (7,13). However, other studies have demonstrated that the prognosis for left hemi-colon cancer is no worse than for other colon cancers, and that left hemi-colectomy is sufficient for a satisfactory oncological outcome (8,9,14). A recent study showed that complete mesocolic excision in the mesocolic plane with central vascular ligation is associated with the removal of more mesocolon and a greater lymph node yield, and might improve 5-year survival (15).…”
Section: Discussionmentioning
confidence: 99%
“…This concern has been varies among surgeons and institutes. Interestingly, Sadler et al [14], advocated extended right colectomy an option for SFC. He believed that lymph nodes metastasis could follow ileocolic artery in SFC but it had been rarely reported, hence then, left colectomy stated as the standard procedure of choice in SFC [2].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, both the SF and the transverse colon were never included in randomized controlled trials designed to assess the efficacy of laparoscopic surgery as a curative treatment for colon cancer [4,5]. The reasons for exclusion of SF cancer from the trials include technical difficulties with laparoscopic identification of the middle and left colic vessels and subsequent lymph node dissection.Other main controversies that contribute to the status of laparoscopic SF resection as a yet nonstandardized procedure involve the appropriate extent of surgery and the risk of inadvertent splenectomy [2,6]. Recommendations for SF cancer range from left partial resection to extended right hemicolectomy in association with splenectomy and distal pancreatectomy [2].…”
mentioning
confidence: 99%
“…Other main controversies that contribute to the status of laparoscopic SF resection as a yet nonstandardized procedure involve the appropriate extent of surgery and the risk of inadvertent splenectomy [2,6]. Recommendations for SF cancer range from left partial resection to extended right hemicolectomy in association with splenectomy and distal pancreatectomy [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation